Corrosion inhibitor for inhibiting magnesium alloy corrosion and application thereof
The corrosion inhibitor of magnesium alloys in automobile coolant is solved by combining 1-octyl-3-methylimidazole L-proline with zinc sulfate or 1-octyl-3-methylimidazole L-proline, sodium dodecyl sarcosine and zinc sulfate, and the corrosion inhibition and environmentally friendly effect is achieved.
Patent Information
- Application Number
- CN202510051805.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-14
- Publication Date
- 2025-04-25
AI Technical Summary
Magnesium alloys are prone to corrosion in automobile coolant, resulting in a shortening of the engine service life. The existing corrosion inhibitors are highly polluted to the environment, and green and environmentally friendly corrosion inhibitors need to be developed.
The corrosion inhibitor obtained by combining 1-octyl-3-methylimidazole L-proline with zinc sulfate or 1-octyl-3-methylimidazole L-proline, sodium dodecyl sarcosine and zinc sulfate is formed to inhibit corrosion of magnesium alloy through mechanisms such as synergistic adsorption, charge regulation and corrosion inhibition.
The corrosion inhibitor has an efficient corrosion inhibition effect, and the corrosion inhibition efficiency can reach 99.33%. Since the composition is a green and environmentally friendly substance, pollution to the environment is avoided.
Smart Images

Figure BDA0005240205790000041 
Figure BDA0005240205790000042 
Figure BDA0005240205790000061
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of metal material anti-corrosion, relates to magnesium alloy anti-corrosion, and specifically relates to a corrosion inhibitor for inhibiting magnesium alloy corrosion and application thereof. Background Art
[0002] The reserves of magnesium in the earth's crust are second only to aluminum and iron, and it is the metal with the smallest specific gravity (specific gravity is 1.73g / cm3). Magnesium and magnesium alloys have excellent specific strength and specific stiffness, and have a series of advantages such as high seismic resistance and electromagnetic shielding performance. Therefore, they have broad application prospects in the fields of automobiles, electronics, aerospace, national defense and military industries. Magnesium alloy engines can significantly reduce the weight and fuel consumption of automobiles and reduce environmental pollution, so magnesium alloys will be an important material for automobile engines.
[0003] However, magnesium is a very active metal with a standard potential of -2.36V at 25°C. Therefore, magnesium and its alloys are not corrosion-resistant in most organic acids, inorganic acids and neutral media. Even in distilled water, magnesium alloys with the surface film removed will also produce hydrogen evolution due to corrosion. Automobile coolant is a circulating heat transfer medium in the engine cooling system. It has multiple functions such as antifreeze, anti-boiling, anti-corrosion, and anti-scaling. It is an indispensable component for the normal and stable operation of the engine. Its performance directly affects the service life of the automobile engine. Therefore, how to inhibit the corrosion of magnesium alloys caused by automobile engine coolant is a technical problem that needs to be solved urgently by those skilled in the art.
[0004] At present, adding corrosion inhibitors to automobile coolants to inhibit magnesium alloy corrosion is a very effective anti-corrosion technology, which has the advantages of easy use, quick effect and high corrosion inhibition efficiency. The most studied magnesium alloy corrosion inhibitors are chromates, phosphates, nitrates, nitrites, etc. Although the corrosion inhibition effect is good, it will cause serious pollution to the environment. Summary of the invention
[0005] In view of the above-mentioned deficiencies in the prior art, the purpose of the present invention is to provide a corrosion inhibitor for inhibiting the corrosion of magnesium alloys and its application. The corrosion inhibitor of the present invention is green and environmentally friendly, has high corrosion inhibition efficiency, and can effectively inhibit the corrosion of magnesium alloys caused by automobile coolant.
[0006] The technical solution of the present invention is achieved in this way:
[0007] A corrosion inhibitor for inhibiting corrosion of a magnesium alloy. The corrosion inhibitor comprises 1-octyl-3-methylimidazole L-proline salt and zinc sulfate, wherein the mass ratio of the 1-octyl-3-methylimidazole L-proline salt to the zinc sulfate is 0.1-2.0:0.01-0.35.
[0008] Furthermore, the corrosion inhibitor also includes sodium lauryl sarcosinate, 1-octyl-3-methylimidazole L-proline salt, sodium lauryl sarcosinate and zinc sulfate in a mass ratio of 0.1-2.0:0.1-0.5:0.01:-0.35.
[0009] Furthermore, the mass ratio of 1-octyl-3-methylimidazole L-proline salt, sodium lauryl sarcosinate and zinc sulfate is 0.5-2.0:0.25-0.5:0.1-0.25.
[0010] Furthermore, the mass ratio of 1-octyl-3-methylimidazole L-proline salt, sodium lauryl sarcosinate and zinc sulfate is 12:4:1.4.
[0011] The above-mentioned corrosion inhibitor for inhibiting corrosion of magnesium alloy is used in the application of automobile coolant.
[0012] Furthermore, the corrosion inhibitor is added to the automobile coolant in an amount of 1 to 3 g / L.
[0013] Furthermore, the automobile coolant is ethylene glycol with a volume fraction of 30 to 70%.
[0014] Compared with the prior art, the present invention has the following beneficial effects:
[0015] 1. The present invention adopts 1-octyl-3-methylimidazole L-proline salt and zinc sulfate or 1-octyl-3-methylimidazole L-proline salt, sodium lauryl sarcosinate and zinc sulfate to obtain a corrosion inhibitor. 1-octyl-3-methylimidazole L-proline salt, sodium lauryl sarcosinate and zinc sulfate are all green and environmentally friendly substances, which can effectively avoid pollution to the environment.
[0016] 2. The complex of 1-octyl-3-methylimidazole L-proline salt and zinc sulfate has a certain corrosion inhibition effect on magnesium alloy, mainly because the two have a synergistic effect. Specifically, the heteroatoms (such as nitrogen and oxygen) in the 1-octyl-3-methylimidazole L-proline salt molecule can produce chemical adsorption with the metal atoms on the surface of the magnesium alloy, and can form an adsorption film on the metal surface, thereby effectively isolating the magnesium alloy from the corrosive medium, thereby reducing the direct contact between the magnesium alloy and the corrosive medium and reducing the corrosion efficiency; at the same time, the adsorption film can provide more adsorption sites for the zinc ions in the zinc sulfate, so that more zinc ions in the zinc sulfate react with the surface of the magnesium alloy to generate insoluble zinc compounds precipitated on the metal surface, thereby enhancing the thickness and density of the adsorption film, further preventing the corrosion of the magnesium alloy by the corrosive medium and improving the corrosion efficiency.
[0017] As a surfactant, sodium lauryl sarcosinate has a hydrophilic group facing the solution and a lipophilic group facing the metal surface, which can increase the coverage and adsorption stability of the corrosion inhibitor on the metal surface and form a second layer of adsorption film. At the same time, sodium lauryl sarcosinate can also change the charge distribution on the surface of the magnesium alloy, making the positive charge more evenly distributed, which is conducive to the adsorption of negatively charged 1-octyl-3-methylimidazole L-proline salt. These three substances have a good corrosion inhibition effect on magnesium alloys through multiple mechanisms such as synergistic adsorption, charge regulation, inhibition of corrosion reactions, improvement of film structure and competitive adsorption.
[0018] 3. The corrosion inhibition efficiency of the corrosion inhibitor of the present invention is as high as 99.33% at 25°C, which has excellent corrosion inhibition efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1-3 Polarization curves of single factor, two-by-two and three-way combination comparative tests of various corrosion inhibitors.
[0020] Figure 2 -Polarization curves of the comparative test of zinc sulfate with different concentrations and 1-octyl-3-methylimidazole L-proline salt.
[0021] Figure 3 -Polarization curves of the comparative test of different concentrations of 1-octyl-3-methylimidazole L-proline salt and zinc sulfate.
[0022] Figure 4-2 Polarization curve of AZ91D magnesium alloy with corrosion inhibitor added in 50% ethylene glycol coolant at 5°C.
[0023] Figure 5-2 Field emission scanning electron microscopy comparison of AZ91D magnesium alloy before and after adding corrosion inhibitor in 50% ethylene glycol coolant at 5°C.
[0024] Figure 6-2 Polarization curves of AZ91D magnesium alloy with inhibitor concentration gradient in 50% ethylene glycol coolant at 5°C. DETAILED DESCRIPTION
[0025] The present invention is further described in detail below in conjunction with the accompanying drawings and specific embodiments.
[0026] Example 1
[0027] Single factor, two-by-two compound and three-by-three compound comparative tests were conducted on the three corrosion inhibitors (1-octyl-3-methylimidazole L-proline salt, sodium lauryl sarcosinate and zinc sulfate) used in the present invention.
[0028] The specific test process is as follows:
[0029] (1) Pretreatment of AZ91D magnesium alloy working electrode
[0030] The AZ91D magnesium alloy sample was processed into a Φ11.3x50 mm cylindrical shape. The entire electrode was encapsulated with epoxy resin, with only 1.0 cm exposed. 2 The working surface is polished with metallographic sandpaper from 200#, 320#, 400#, 600#, 800#, 1000#, 1200#, degreased with acetone, cleaned with ethanol, and then placed in cold air to dry for use.
[0031] (2) Preparation of test solution
[0032] A 50% (volume fraction) ethylene glycol system was used, and the corrosive aqueous solution was prepared with reference to ASTM D1384-96 (148 mg / L Na2SO4+138 mg / L NaHCO3+165 mg / L NaCl).
[0033] The remaining solutions were a: 0.5 g / L 1-octyl-3-methylimidazole L-proline salt;
[0034] b: 0.25 g / L sodium lauryl sarcosinate;
[0035] c: 0.25 g / L zinc sulfate;
[0036] d: 0.5 g / L 1-octyl-3-methylimidazole L-proline salt + 0.25 g / L sodium lauryl sarcosinate;
[0037] e: 0.5 g / L 1-octyl-3-methylimidazole L-proline salt + 0.25 g / L zinc sulfate;
[0038] f: 0.25g / L sodium lauryl sarcosinate + 0.25g / L zinc sulfate;
[0039] g: 0.5g / L 1-octyl-3-methylimidazole L-proline salt + 0.25g / L sodium lauryl sarcosinate + 0.25g / L zinc sulfate.
[0040] (3) Test instruments and methods
[0041] The corrosion inhibition performance of the corrosion inhibitor was tested by the potentiodynamic scanning technology in the Tunliqiang 1287 electrochemical test system: a three-electrode system was adopted, with the treated AZ91D magnesium alloy as the working electrode, the Pt sheet as the auxiliary electrode, and the saturated calomel electrode as the reference electrode; the potential scanning range of the potentiodynamic polarization curve test was about -0.30 (vs OCP) ~ +0.30 (vs OCP) V, and the scanning speed was 0.5mv﹒ s -1The test frequency range of electrochemical impedance spectroscopy is 0.01~100KHz, and the AC excitation signal is a 5mV sine wave. The test is carried out at 25℃, 50% (volume fraction) ethylene glycol system after 0.5h at open circuit potential.
[0042] (4) Test results
[0043] The corrosion inhibition effect of the corrosion inhibitor can be calculated using the corrosion current density corresponding to the polarization curve:
[0044]
[0045] Wherein, η represents the corrosion inhibition efficiency of the corrosion inhibitor; I0 represents the corrosion current density of the metal in the medium when no corrosion inhibitor is added; I represents the corrosion current density of the metal in the medium when the corrosion inhibitor is added.
[0046] See also Figure 1 , Figure 1 It is the polarization curve diagram of the comparative test of single factor, two-by-two combination and three-way combination of three corrosion inhibitors.
[0047] Curve a represents 0.5 g / L 1-octyl-3-methylimidazole L-proline salt;
[0048] Curve b represents 0.25 g / L sodium lauryl sarcosinate;
[0049] Curve c represents 0.25 g / L zinc sulfate;
[0050] Curve d represents 0.5 g / L 1-octyl-3-methylimidazole L-proline salt + 0.25 g / L sodium lauryl sarcosinate;
[0051] Curve e represents 0.5 g / L 1-octyl-3-methylimidazole L-proline salt + 0.25 g / L zinc sulfate;
[0052] Curve f represents 0.25 g / L sodium lauryl sarcosinate + 0.25 g / L zinc sulfate;
[0053] Curve g represents 0.5 g / L 1-octyl-3-methylimidazole L-proline salt + 0.25 g / L sodium lauryl sarcosinate + 0.25 g / L zinc sulfate;
[0054] Curve h represents a 50% (volume fraction) ethylene glycol blank solution.
[0055] As can be seen from Figure 1, when 1-octyl-3-methylimidazole L-proline salt, sodium lauryl sarcosine and zinc sulfate exist alone in the solution, they do not have a significant corrosion inhibition effect on AZ91D magnesium alloy; when they are compounded in pairs, only 1-octyl-3-methylimidazole L-proline salt, sodium lauryl sarcosine and zinc sulfate have a significant corrosion inhibition effect on AZ91D magnesium alloy.
[0056] -3-Methylimidazole L-proline salt and zinc sulfate greatly reduce the cathode polarization curve, indicating that these two substances may be cathode corrosion inhibitors when combined. When the three are combined, the corrosion potential shifts positively, the corrosion current decreases, and the anodic polarization curve and the cathodic polarization curve are significantly reduced, indicating that the combination of these three substances has a significant corrosion inhibition effect, and there is a synergistic effect between the corrosion inhibitors, forming a mixed corrosion inhibitor. The corresponding electrochemical data are listed in Table 1
[0057] Table 1: Corrosion potential, corrosion current and inhibition efficiency of AZ91D magnesium alloy in three corrosion inhibitors as single factor, two-two combination and three-way combination
[0058]
[0059] As can be seen from the table, when 1-octyl-3-methylimidazole L-proline salt, sodium lauryl sarcosine and zinc sulfate are added separately, the corrosion inhibition efficiency is low, and the corrosion inhibition effect on magnesium alloy is very limited. When compounded in pairs, only when 1-octyl-3-methylimidazole L-proline salt and zinc sulfate are combined, the corrosion inhibition rate is significantly increased, and the corrosion inhibition efficiency reaches 94.70%. In combination with the polarization curve, it can be seen that the combination of these two substances mainly controls the cathode process. When the three substances are combined, the corrosion inhibition efficiency increases to 96.86%. It shows that when 1-octyl-3-methylimidazole L-proline salt and zinc sulfate are combined, they have good corrosion inhibition efficiency for magnesium alloys. When these three substances are compounded, they have a better corrosion inhibition effect, which reflects the synergistic effect between corrosion inhibitors.
[0060] Example 2
[0061] Comparative test of zinc sulfate and 1-octyl-3-methylimidazole L-proline salt.
[0062] (1) The pretreatment of the AZ91D magnesium alloy working electrode is the same as in Example 1.
[0063] (2) Preparation of test solution
[0064] A 50% (volume fraction) ethylene glycol system was used, and the etching aqueous solution was the same as in Example 1.
[0065] The remaining solutions were a: 0.1 g / L 1-octyl-3-methylimidazole L-proline salt + 0.25 g / L zinc sulfate;
[0066] b: 0.3 g / L 1-octyl-3-methylimidazole L-proline salt + 0.25 g / L zinc sulfate;
[0067] c: 0.5 g / L 1-octyl-3-methylimidazole L-proline salt + 0.25 g / L zinc sulfate;
[0068] d: 1.0 g / L 1-octyl-3-methylimidazole L-proline salt + 0.25 g / L zinc sulfate;
[0069] e: 1.5 g / L 1-octyl-3-methylimidazole L-proline salt + 0.25 g / L zinc sulfate;
[0070] f: 2.0 g / L 1-octyl-3-methylimidazole L-proline salt + 0.25 g / L zinc sulfate;
[0071] g: 0.5 g / L 1-octyl-3-methylimidazole L-proline salt + 0.025 g / L zinc sulfate;
[0072] h: 0.5 g / L 1-octyl-3-methylimidazole L-proline salt + 0.05 g / L zinc sulfate;
[0073] i: 0.5 g / L 1-octyl-3-methylimidazole L-proline salt + 0.1 g / L zinc sulfate;
[0074] j: 0.5 g / L 1-octyl-3-methylimidazole L-proline salt + 0.15 g / L zinc sulfate;
[0075] k: 0.5 g / L 1-octyl-3-methylimidazole L-proline salt + 0.2 g / L zinc sulfate.
[0076] (3) Test instruments and methods
[0077] Same as Example 1.
[0078] (4) Test results
[0079] See also Figure 2 , Figure 2 This is a polarization curve diagram of the comparative test of different concentrations of 1-octyl-3-methylimidazole L-proline salt and zinc sulfate.
[0080] As can be seen from Figure 2, as the concentration of 1-octyl-3-methylimidazole L-proline salt increases, the corrosion potential shifts positively and the anodic curve shifts to the left, indicating that increasing the concentration of 1-octyl-3-methylimidazole L-proline salt is beneficial to slowing down the corrosion of magnesium alloys, and mainly inhibiting the anodic area. The corresponding electrochemical data are listed in Table 2.
[0081] Table 2: Polarization curve fitting parameters of different concentrations of 1-octyl-3-methylimidazole L-proline salt and zinc sulfate
[0082]
[0083] It can be seen from Table 2 that with the increase of the concentration of 1-octyl-3-methylimidazole L-proline salt, the corrosion current density decreases. When the concentration is less than 0.5g / L, the corrosion inhibition efficiency is not very high. When the concentration is 1.5g / L, the corrosion current density reaches the minimum, and the corrosion inhibition efficiency reaches 92.59%. When the concentration increases to 2.0g / L, the corrosion current density increases again, and the corrosion inhibition efficiency drops to 90.59%, indicating that the increase in the concentration of 1-octyl-3-methylimidazole L-proline salt will enhance the synergistic effect with zinc sulfate. When the two are compounded, the corrosion inhibition efficiency is highest when the concentration of 1-octyl-3-methylimidazole L-proline salt is 1.5g / L.
[0084] Figure 3 It is a polarization curve diagram of the comparative test of zinc sulfate with different concentrations and 1-octyl-3-methylimidazole L-proline salt. As can be seen from Figure 3, with the increase of zinc sulfate concentration, the corrosion potential shifts positively and the anode curve shifts left, indicating that the corrosion tendency gradually decreases, and it is also mainly inhibited by the anode area. When the zinc sulfate concentration is 0.1g / L, the corrosion potential is the smallest. It shows that the increase of zinc sulfate concentration will enhance the synergistic effect with 1-octyl-3-methylimidazole L-proline salt, but when the concentration exceeds 0.1g / L, the corrosion potential shifts slightly to the negative side, and the corrosion tendency begins to increase, indicating that the appropriate addition of zinc sulfate is conducive to enhancing the corrosion inhibition effect, but exceeding a certain concentration will inhibit the corrosion inhibition effect. The corresponding electrochemical data are listed in Table 3.
[0085] Table 3: Polarization curve fitting parameters of different concentrations of zinc sulfate and 1-octyl-3-methylimidazole L-proline salt
[0086]
[0087] It can be seen from Table 3 that different concentrations of zinc sulfate and 1-octyl-3-methylimidazole L-proline salt have a certain corrosion inhibition effect. As the concentration of zinc sulfate increases, the corrosion potential gradually increases, the corrosion current density decreases, and the corrosion inhibition efficiency gradually increases from 63.03% to 84.49%. When the concentration exceeds 0.1 g / L, the corrosion current density increases and the corrosion inhibition efficiency decreases to 81.42%.
[0088] Example 3
[0089] (1) The pretreatment of the AZ91D magnesium alloy working electrode is the same as in Example 1.
[0090] (2) Preparation of test solution
[0091] A 50% (volume fraction) ethylene glycol system was used, and the corrosion aqueous solution was the same as in Example 1. 9 groups of 1-octyl-3-methylimidazole L-proline salt (A), sodium lauryl sarcosinate (B) and zinc sulfate (C) were prepared at different concentrations, as shown in Table 4.
[0092] (3) Test instruments and methods
[0093] Same as Example 1.
[0094] In order to quickly select the best corrosion inhibitor formula, we can choose orthogonal experiment. Orthogonal experiment is an efficient method in the optimization of corrosion inhibitor formula. It can comprehensively examine the influence of multiple factors and their different levels on the corrosion inhibition effect in a relatively small number of experiments by reasonably arranging experiments.
[0095] Factor selection and level setting:
[0096] Three corrosion inhibitors are available: corrosion inhibitor A (1-octyl-3-methylimidazole L-proline salt), corrosion inhibitor B (12
[0097] Sodium alkyl sarcosinate), corrosion inhibitor C (zinc sulfate);
[0098] The concentration of A was set at three levels: 2.0 g / L, 1.6 g / L, and 1.2 g / L;
[0099] The concentration of B was set at 3 levels: 0.45 g / L, 0.40 g / L, and 0.35 g / L;
[0100] The concentration of C was set at three levels: 0.22 g / L, 0.18 g / L, and 0.14 g / L;
[0101] For a four-factor three-level experiment, we can use L9(3 4 ) Orthogonal table. This orthogonal table has 9 rows, indicating that 9 experiments need to be done, and 4 columns correspond to four factors (usually one blank factor is considered), and each factor has 3 levels.
[0102] (4) Test results
[0103] Table 4 shows the orthogonal test results.
[0104] Table 4 Corrosion inhibition rate of three substances at different concentrations
[0105]
[0106] It can be seen from Table 4 that the corrosion inhibitor obtained by compounding 1-octyl-3-methylimidazole L-proline salt, sodium lauryl sarcosinate and zinc sulfate has a good corrosion inhibition effect on magnesium alloy, and the corrosion inhibition rate is the highest when the concentration of 1-octyl-3-methylimidazole L-proline salt is 1.2 g / L, the concentration of sodium lauryl sarcosinate is 0.40 g / L and the concentration of zinc sulfate is 0.14 g / L.
[0107] See also Figure 4 , Figure 4The polarization curves of AZ91D magnesium alloy in 50% (volume fraction) ethylene glycol blank solution and the 8th group of corrosion inhibitors at 25°C are shown in Figure 2. Figure 2 It can be seen that after adding the corrosion inhibitor, the corrosion potential shifts positively, the corrosion current density decreases, and the anodic polarization curve and the cathodic polarization curve decrease significantly, indicating that the compounded corrosion inhibitor of the present invention is a mixed corrosion inhibitor. The corresponding electrochemical data are listed in Table 5.
[0108] Table 5: Corrosion potential, corrosion current and corrosion inhibition efficiency of AZ91D magnesium alloy in 50% (volume fraction) ethylene glycol system for 0.5h
[0109]
[0110] Figure 5 The left and right pictures are field emission scanning electron microscope comparison pictures before and after adding the 8th group of corrosion inhibitors. Figure 5 It can be seen that the magnesium alloy without adding corrosion inhibitor is corroded in 50% ethylene glycol coolant, and obvious corrosion cracks appear. After adding the corrosion inhibitor, a protective film is formed on the surface, which inhibits the corrosion of the magnesium alloy. The corrosion inhibition efficiency of the compounded corrosion inhibitor of the present invention can reach up to 99.33%, which greatly improves the corrosion resistance of AZ91D magnesium alloy in 50% (volume fraction) ethylene glycol system, and provides a reliable solution for the material protection of magnesium alloy in engine coolant.
[0111] Example 4
[0112] The formulation of the present invention was subjected to a concentration gradient test.
[0113] (1) The pretreatment of the AZ91D magnesium alloy working electrode is the same as in Example 1.
[0114] (2) Preparation of test solution
[0115] A 50% (volume fraction) ethylene glycol system was used, and the corrosive aqueous solution was prepared with reference to ASTM D1384-96 (148 mg / L Na2SO4+138 mg / L NaHCO3+165 mg / L NaCl).
[0116] The remaining solutions are:
[0117] a: 0.60 g / L 1-octyl-3-methylimidazole L-proline salt + 0.20 g / L sodium lauryl sarcosinate + 0.07 g / L zinc sulfate;
[0118] b: 0.30 g / L 1-octyl-3-methylimidazole L-proline salt + 0.10 g / L sodium lauryl sarcosine + 0.035 g / L zinc sulfate;
[0119] c: 0.15 g / L 1-octyl-3-methylimidazole L-proline salt + 0.05 g / L sodium lauryl sarcosinate + 0.0175 g / L zinc sulfate;
[0120] d: 0.075 g / L 1-octyl-3-methylimidazole L-proline salt + 0.025 g / L sodium lauryl sarcosinate + 0.00875 g / L zinc sulfate.
[0121] (3) Test instruments and methods
[0122] Same as Example 1.
[0123] (4) Test results
[0124] See also Figure 6 , Figure 6 It is the polarization curve of the corrosion inhibitor concentration gradient of AZ91D magnesium alloy in 50% ethylene glycol coolant at 25°C. Among them:
[0125] Curve a represents 0.075 g / L 1-octyl-3-methylimidazole L-proline salt + 0.025 g / L sodium lauryl sarcosinate + 0.00875 g / L zinc sulfate;
[0126] Curve b represents 0.15 g / L 1-octyl-3-methylimidazole L-proline salt + 0.05 g / L sodium lauryl sarcosinate + 0.0175 g / L zinc sulfate;
[0127] Curve c represents 0.30 g / L 1-octyl-3-methylimidazole L-proline salt + 0.10 g / L sodium lauryl sarcosinate + 0.035 g / L zinc sulfate;
[0128] Curve d represents 0.60 g / L 1-octyl-3-methylimidazole L-proline salt + 0.20 g / L sodium lauryl sarcosinate + 0.07 g / L zinc sulfate;
[0129] Curve e represents 1.2 g / L 1-octyl-3-methylimidazole L-proline salt + 0.40 g / L sodium lauryl sarcosinate + 0.14 g / L zinc sulfate;
[0130] Curve f represents a 50% (volume fraction) ethylene glycol blank solution.
[0131] Depend on Figure 6 It can be seen that as the concentration of magnesium alloy corrosion inhibitor increases, its anodic polarization curve and cathodic polarization curve gradually decrease, and the corrosion potential gradually shifts positively, indicating that the corrosion inhibition efficiency gradually increases.
[0132] The corresponding electrochemical data are listed in Table 5 below.
[0133] Table 5: Corrosion potential, corrosion current and corrosion inhibition efficiency of AZ91D magnesium alloy in 50% (volume fraction) ethylene glycol system with varying concentrations
[0134]
[0135] It can be seen from the data in Table 5 that as the concentration of the corrosion inhibitor increases, the corrosion potential gradually shifts positively, the corrosion current gradually decreases, and the corresponding corrosion inhibition efficiency gradually increases.
[0136] Finally, it should be noted that the above embodiments of the present invention are only examples for illustrating the present invention, and are not intended to limit the implementation methods of the present invention. For those skilled in the art, other different forms of changes and modifications can be made based on the above description. It is impossible to list all implementation methods here. Any obvious changes or modifications derived from the technical solution of the present invention are still within the scope of protection of the present invention.
Claims
1. A corrosion inhibitor for inhibiting corrosion of magnesium alloys, characterized in that: The corrosion inhibitor comprises 1-octyl-3-methylimidazole L-proline salt and zinc sulfate, and the mass ratio of 1-octyl-3-methylimidazole L-proline salt to zinc sulfate is 0.1-2.0:0.01-0.
35.
2. The corrosion inhibitor for inhibiting corrosion of magnesium alloy according to claim 1, characterized in that: The corrosion inhibitor also includes sodium lauryl sarcosinate, 1-octyl-3-methylimidazole L-proline salt, sodium lauryl sarcosinate and zinc sulfate in a mass ratio of 0.1-2.0:0.1-0.5:0.01:-0.
35.
3. The corrosion inhibitor for inhibiting corrosion of magnesium alloy according to claim 2, characterized in that: The mass ratio of 1-octyl-3-methylimidazole L-proline salt, sodium lauryl sarcosinate and zinc sulfate is 0.5-2.0:0.25-0.5:0.1-0.
25.
4. The corrosion inhibitor for inhibiting corrosion of magnesium alloy according to claim 3, characterized in that: The mass ratio of 1-octyl-3-methylimidazole L-proline salt, sodium lauryl sarcosinate and zinc sulfate is 12:4:1.
4.
5. Use of the corrosion inhibitor for inhibiting corrosion of magnesium alloy according to any one of claims 1 to 4 in automobile coolant.
6. The use of a corrosion inhibitor for inhibiting corrosion of magnesium alloy according to claim 5, characterized in that: The corrosion inhibitor is added to the automobile coolant at a dosage of 1 to 3 g / L.
7. The use of a corrosion inhibitor for inhibiting corrosion of magnesium alloy according to claim 6, characterized in that: The automobile coolant is ethylene glycol with a volume fraction of 30 to 70%.